Kyoto visual culture in the early Edo and Meiji periods the arts of reinvention - Pitelka, Morgan 1972-; Tseng, Alice Yu-Ting (Routledge studies in the modern history of Asia, 2016)
"The city of Kyoto has undergone radical shifts in its significance as a political and cultural centre, as a hub of the national bureaucracy, as a symbolic and religious centre, and as a site for the production and display of art. However, the field of Japanese history and culture lacks a book which considers Kyoto on its own terms as a historic city with a changing identity. Examining cultural production in the city of Kyoto in two periods of political transition, this book promises to be a major step forward in advancing our knowledge of Kyoto's history and culture. Its chapters focus on two centuries in Kyoto's history in which the old capital was politically marginalised: the seventeenth century, when the centre of power shifted from the old imperial capital to the new warriors' capital of Edo; and the nineteenth century, when the imperial court itself was moved to the new modern centre of Tokyo. The contributors argue that in both periods the response of Kyoto elites--emperors, courtiers, tea masters, municipal leaders, monks, and merchants--was artistic production and cultural revival. As an artistic, cultural and historical study of Japan's most important historic city, this book will be invaluable to students and scholars of Japanese history, Asian history, the Meiji and Edo periods, art history, visual culture and cultural history"--Provided by publisher.